Effects of ECM proteins (laminin, fibronectin, and type IV collagen) on the biological behavior of Schwann cells and their roles in the process of remyelination after peripheral nerve injury - Yu, Peng; Zhang, Guanhua; Hou, Bo; Song, Enpeng; Wen, Jiaming; Ba, Yueyang; Zhu, Donglin; Wang, Gangwei; Qin, Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: It is important to note that complete myelination and formation of myelinated fibers are essential for functional nerve regeneration after peripheral nerve injury (PNI). However, suboptimal myelin regeneration is common and can hinder ideal nerve regeneration. Therefore, it is important to closely monitor and support myelin regeneration in patients with PNI to achieve optimal outcomes. Methods: This study analyzed the effects of three extracellular matrix (ECM) proteins on Schwann cells (SCs) in the nerve regeneration environment, including their adhesion, proliferation, and migration. The study also explored the use of composite sodium alginate hydrogel neural scaffolds with ECM components and investigated the effects of ECM proteins on remyelination following peripheral nerve injury. Results: The results showed that laminin (LN), fibronectin (FN), and collagen Ⅳ (type IV Col) promoted the early adhesion of SCs in 2-dimensional culture but the ratios of early cell adhesion were quite different and the maintenance of cells’ morphology by different ECM proteins were significantly different. In transwell experiment, the ability of LN and FN to induce the migration of SCs was obviously higher than that of type IV Col. An vitro co-culture model of SCs and dorsal root ganglia (DRG) neurons showed that LN promoted the transition of SCs to a myelinated state and the maturation of the myelin sheath, and increased the thickness of neurofilaments. Animal experiments showed that LN had superior effects in promoting myelin sheath formation, axon repair, and reaching an ideal G-ratio after injury compared to FN and Col IV. The situation of gastrocnemius atrophy was significantly better in the LN group. Notably, the thickness of the regenerated myelin sheaths in the type IV Col group was the thickest. Conclusion: In this experiment, we analyzed and compared the effects of LN, FN, and type IV Col on the biological behavior of SCs and their effects on remyelination after PNI and further clarified their unique roles in the process of remyelination. Further research is necessary to explore the underlying mechanisms.